Una riflessione teologica sulla condizione di chi non ha potuto (ancora) sposarsi - Valenzisi, Manuel (La scuola cattolica, 2025)
The number of people who live outside of marriage or in a stable relationship, and who do not choose celibacy as a form of consecration, is increasing. The existential reasons at the basis of the diversified identity of being single are many. This article came into being thanks to the conviction that theology has to also reflect on the existential conditions of these people. Having examined some data and sociological considerations regarding the reasons behind the increase in the conditions of life in solitude (singleness) in globalized society, we will undertake a theological reflection, focusing our attention in particular on the baptized who, for reasons outwith their control, have not been able to marry and who do not feel called to express their belonging to the Lord in different ways from the baptism they have received.